Association Between Colonic Diverticulosis and Erectile Dysfunction: A Nationwide Population-Based Study. Issue 47 (November 2015) - Chen, Chia-Chang; Su, Jiann-Sheng; Yeh, Hong-Zen; Chang, Chi-Sen; Peng, Yen-Chun; Tseng, Chih-Wei; Chen, Yu-Tso; Lin, Cheng-Li; Kao, Chia-Hung
Abstract : Abstract: We investigated whether colonic diverticulosis (CD) is associated with an increased risk of the subsequent development of erectile dysfunction (ED). We identified 2879 patients, diagnosed with CD between 1998 and 2011 from the Taiwan National Health Insurance Research Database as the study cohort. Patients in a comparison cohort were frequency-matched with those in the CD cohort at a ratio of 1:4, frequency matched according to age (in 5-year bands) and year of CD diagnosis. The patients were followed-up until ED development, withdrawal from the National Health Insurance system, or the end of 2011. For both cohorts, the overall and age-specific incidence density rates of ED (per 1000 person-years) were calculated. The effects of age, CD, and other comorbidities on the risk of ED development were examined using Cox proportional hazards regression models. The average follow-up durations were 4.76 years and 4.97 years for the CD patients and comparison cohorts, respectively. The overall incidence of ED was 1.70-fold higher in the CD cohort than in the comparison cohort (2.92 and 1.71 per 1000 person-years, respectively). Colonic diverticulosis was an independent risk factor for subsequent ED development (adjusted HR [aHR] = 1.56, 95% confidence interval = 1.07–2.28) in a multivariate Cox proportional hazards regression model. In this large retrospective cohort study, CD was associated with future ED development. Additional studies are required for validating our results.